Sulforaphane alleviates psoriasis by enhancing antioxidant defense through KEAP1-NRF2 Pathway activation and attenuating inflammatory signaling - Chujun Ma; Chaode Gu; Panpan Lian; Junaid Wazir; Renwei Lu; Binjia Ruan; Lulu Wei; Li Li; Wenyuan Pu; Ziqi Peng; Wentong Wang; Yangyongyi Zong; et al. (Cell Death and Disease, 2023)
Abstract Psoriasis is a chronic inflammatory skin disease that affects millions of people worldwide. Sulforaphane (SFN) has been shown to have anti-inflammatory and antioxidant properties. In this study, we investigated the effects of SFN on a mouse model of psoriasis induced by imiquimod (IMQ) and its underlying molecular mechanism. Mice treated with SFN showed significant improvement in psoriatic symptoms, including reduced erythema, scales, and cutaneous thickness. Histopathological analysis and immunohistochemical staining revealed decreased expression of K16, K17, and Ki67 in SFN-treated mice, indicating reduced abnormal differentiation of keratinocytes and cutaneous inflammation. SFN treatment also reduced the activation of STAT3 and NF-κB pathways and downregulated pro-inflammatory cytokines IL-1β, IL-6, and CCL2. In vitro experiments using HaCaT cells demonstrated that SFN inhibited IL-22 and TNF-α-induced activation of inflammatory pathways and keratinocyte proliferation. Network pharmacology analysis suggested that the KEAP1-NRF2 pathway might be involved in the protective effects of SFN on psoriasis. We observed reduced NRF2 expression in human psoriatic lesions, and subsequent experiments showed that SFN activated KEAP1-NRF2 pathway in vivo and in vitro. Importantly, NRF2-deficient mice exhibited aggravated psoriasis-like symptoms and reduced response to SFN treatment. Our findings indicate that SFN ameliorates psoriasis symptoms and inflammation through the KEAP1-NRF2 pathway, suggesting a potential therapeutic role for SFN in the treatment of psoriasis.